1992
DOI: 10.1111/j.1365-2249.1992.tb05867.x
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular immune deposits in murine lupus models may contain histones

Abstract: SUMMARYTwo types of lupus mice, NZB/NZW F, female hybrids and mice with graft-versus-host disease (GVHD), were studied. Histones H3 and H2A were detected by immunofluorescence in glomeruli of 22/22 proteinuric GVHD and 8/12 proteinuric NZB/W F, female mice; in non-proteinuric animals, 3/5 GVHD and 2/27 NZB/W F, female were positive. Using antibodies to histone peptides it was shown that mainly the N-terminal regions of histones H3 and H2A were exposed in glomerular deposits. Western blot analysis revealed anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…It has been described that serum AHA levels significantly decrease just before the appearance of glomerular injury and proteinuria, suggesting that AHA may bind to unsaturated epitopes of the autoantigen in target organs (2). Using rabbit Abs to H2A and H3 histone peptides and mAbs, immune deposits containing histones have been detected in both glomerular and epidermal basement membranes of lupus patients (3,4) as well as in the kidneys from NZB/W mice and mice with graft-versus-host disease (5). Furthermore, it was reported that patients with both initial anti-DNA Ab and AHA reactivity have a greater risk of developing proliferative glomerulonephritis (6).…”
mentioning
confidence: 96%
“…It has been described that serum AHA levels significantly decrease just before the appearance of glomerular injury and proteinuria, suggesting that AHA may bind to unsaturated epitopes of the autoantigen in target organs (2). Using rabbit Abs to H2A and H3 histone peptides and mAbs, immune deposits containing histones have been detected in both glomerular and epidermal basement membranes of lupus patients (3,4) as well as in the kidneys from NZB/W mice and mice with graft-versus-host disease (5). Furthermore, it was reported that patients with both initial anti-DNA Ab and AHA reactivity have a greater risk of developing proliferative glomerulonephritis (6).…”
mentioning
confidence: 96%
“…Positive glomerular fluorescence was seen in 22/22 proteinuric and 3/5 non-proteinuric mice using rabbit antibodies to histone peptides 1 21 of H3 and 1 9 of H2A (not shown; see [11]}. Deposits of histones were always accompanied by autologous IgG and C3.…”
Section: Immunoftuorescence Studies On Kidney Sectionsmentioning
confidence: 99%
“…Deposits of histones were always accompanied by autologous IgG and C3. No significant reaction was seen using antibodies to ubiquitin and peptide T4 [11]. A number of rabbit antisera to other histone peptides gave a negative reaction [11].…”
Section: Immunoftuorescence Studies On Kidney Sectionsmentioning
confidence: 99%
See 2 more Smart Citations